Ube2i deletion in adipocytes causes lipoatrophy in mice - Aaron R. Cox; Natasha Chernis; Kang Ho Kim; Peter M. Masschelin; Pradip K. Saha; Shawn M. Briley; Robert Sharp; Xin Li; Jessica B. Felix; Zheng Sun; David D. Moore; Stephanie A. Pangas; et al. (Elsevier, 2021)
Objective: White adipose tissue (WAT) expansion regulates energy balance and overall metabolic homeostasis. The absence or loss of WAT occurring through lipodystrophy and lipoatrophy contributes to the development of hepatic steatosis and insulin resistance. We previously demonstrated that sole small ubiquitin-like modifier (SUMO) E2-conjugating enzyme Ube2i represses human adipocyte differentiation. The role of Ube2i during WAT development remains unknown. Methods: To determine how Ube2i impacts body composition and energy balance, we generated adipocyte-specific Ube2i knockout mice (Ube2ia-KO). CRISPR/Cas9 gene editing inserted loxP sites flanking exons 3 and 4 at the Ube2i locus. Subsequent genetic crosses to Adipoq-Cre transgenic mice allowed deletion of Ube2i in white and brown adipocytes. We measured multiple metabolic endpoints that describe energy balance and carbohydrate metabolism in Ube2ia-KO and littermate controls during postnatal growth. Results: Surprisingly, Ube2ia-KO mice developed hyperinsulinemia and hepatic steatosis. Global energy balance defects emerged from dysfunctional WAT marked by pronounced local inflammation, loss of serum adipokines, hepatomegaly, and near absence of major adipose tissue depots. We observed progressive lipoatrophy that commences in the early adolescent period. Conclusions: Our results demonstrate that Ube2i expression in mature adipocytes allows WAT expansion during postnatal growth. Deletion of Ube2i in fat cells compromises and diminishes adipocyte function that induces WAT inflammation and ectopic lipid accumulation in the liver. Our findings reveal an indispensable role for Ube2i during white adipocyte expansion and endocrine control of energy balance.